Strategy For Character Development Of Akhlaq Al-Karimah Through Hizbul Wathan In Students Of Mts Muhammadiyah Tegalrejo Village, Tugumulyo, Musirawas - Soleman, Soleman; Khozin, Khozin; Hakim, Rahmad (Jurnal Edusci, 2025)
The aim of this study is to explore strategies for developing the character of akhlaq al-karimah (noble morals) through the Hizbul Wathan activity program for MTS students in Tegalrejo Village, Tugumulyo, Musi Rawas. This research uses a qualitative approach with a case study design. The study was conducted at MTS Tegalrejo, located in Tugumulyo District, Musi Rawas Regency. The research subjects include students, school principals, and Hizbul Wathan mentors. Data were collected through interviews, observations, and documentation. Findings from the study reveal that the implementation of the Hizbul Wathan program at MTS Tegalrejo is effective in shaping students' character, promoting qualities such as good morality, trustworthiness, discipline, responsibility, independence, and humility. Through a variety of activities—including marching drills (PBB), pioneering, camping, games, and religious tourism—students acquire not only practical skills but also essential values that foster teamwork, leadership, and personal integrity